2019
DOI: 10.3889/oamjms.2019.186
|View full text |Cite
|
Sign up to set email alerts
|

A Comparing of Tp-Te Interval and Tp-Te/Qt Ratio in Patients with Preserved, Mid-Range and Reduced Ejection Fraction Heart Failure

Abstract: BACKGROUND: Heart failure (HF) is classified in three class: HF with preserved EF (HFpEF); normal or LVEF ≥ 50%, HF with reduced EF (HFrEF); LEVF < 40% and newly HF mid-range EF (HFmrEF); LVEF 40-49%. On Electrocardiography (ECG) T wave, Tpeak-Tend (Tp-Te) interval reflects transmural dispersion of repolarisation (TDR) which of these indexes have been proposed as predictors of risk for ventricular arrhythmia (VA) in many cardiac diseases. AIM: Aim of this study to asses these indices of TDR among thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…It was also found that in patients with heart failure with a reduced ejection fraction (HFrEF), mean Tp-e and its standard deviation were higher than in those with heart failure with preserved ejection fraction (HFpEF) [ 82 ]. However, Son et al found no difference in Tp-e and Tp-e/QT ratio based on ejection fraction in three groups of heart failure patients (preserved, midrange, and reduced ejection fraction) [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was also found that in patients with heart failure with a reduced ejection fraction (HFrEF), mean Tp-e and its standard deviation were higher than in those with heart failure with preserved ejection fraction (HFpEF) [ 82 ]. However, Son et al found no difference in Tp-e and Tp-e/QT ratio based on ejection fraction in three groups of heart failure patients (preserved, midrange, and reduced ejection fraction) [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…26 Tend corrected independent predictive factors on the risk of the incidence of sudden cardiac arrest, in which the value of> 90 ms had a significant correlation with the incidence of sudden cardiac arrest. [28][29][30] Some studies also studied duration TpeakT-late in conditions of myocardial infarction or ischemia. Conlon and colleagues found an increase in the duration ofT-thepeakTfinal in patients with coronary artery ataxia.…”
Section: P-wave Dispersionmentioning
confidence: 99%